The Role of Intelligence in Female Face Perception: Verbal NotVisual-Spatial IQ Intervenes with Intelligence Assessment in Face Composites - Demuthova, Slavka; Demuth, Andrej (European Scientific Journal, ESJ, 2017)
Study concentrates on the relation between intelligence (verbal and visual-spatial) of the observers and their ability to detect the intelligence from the face features of the others. It also studies the connection of intelligence of the observer with their preferences for attractiveness of the female faces, which differ in the levels of visible intelligence. Subjects involved in the study were 415 Slovaks (all of European race; 284 (68,4%) females) with the mean age 21,39 years (st. dev=6,254). Results show, that people who detect the intelligence from the female face composite better, score higher in intelligence than the others. Also, subject who assigned as the prettiest the face which was the most intelligent scored significantly higher in intelligence as those who were attracted more by middle and low intelligent faces. An important finding is, that observed connection applies for verbal intelligence only and not for visual-spatial intelligence.